2009
DOI: 10.1080/02668730902920389
|View full text |Cite
|
Sign up to set email alerts
|

The dance of dissent: Managing conflict in healthcare organizations

Abstract: In this paper, I will suggest that healthcare institutions are intolerant of dissent, and use scapegoating as a defence. When dissent involves criticism of the organization, including whistle-blowing activities, the dissenter is likely to be punished and excluded. I will suggest that this process represents a paranoid defence in which the organization acts as an antigroup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Similarly, Anteby (2010) observed that, in the context of US trade in human cadavers for medical education, anatomists distanced themselves from body brokers to define their own practices as moral and legitimate. In our study, community members leveraged the stories of ‘charlatans’ and ‘magicians’ that posed as mystics to identify more radical groups and scapegoat them (Sarkar, 2009). By excluding certain groups from the bounds of legitimate mysticism, community members shifted attention and blame (Suchman, 1995) and, by comparison, gained a sense of normalcy.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Anteby (2010) observed that, in the context of US trade in human cadavers for medical education, anatomists distanced themselves from body brokers to define their own practices as moral and legitimate. In our study, community members leveraged the stories of ‘charlatans’ and ‘magicians’ that posed as mystics to identify more radical groups and scapegoat them (Sarkar, 2009). By excluding certain groups from the bounds of legitimate mysticism, community members shifted attention and blame (Suchman, 1995) and, by comparison, gained a sense of normalcy.…”
Section: Discussionmentioning
confidence: 99%
“…These evolving "creative partnerships" obviously do not exist within a vacuum, but rather are set within a wider healthcare setting. Sarkar (2009) suggests that healthcare organizations are prone to scapegoating because of the existence of anxious and rigid bureaucracies, together with an incoherent admixture of rigid dominance hierarchies and flattened team approaches. This picture contrasts sharply with the flexible, coherent structure of NETBT and the creative relationships promoted within SUN, such that the model itself may be subject to scapegoating arising from unconscious envious attacks by the organization.…”
Section: Therapeutic Community Principlesmentioning
confidence: 99%